Factors influencing dignity impairment in elderly patients with incontinence-associated dermatitis: A lasso and logistic regression approach - Jinlei Du; Xiaoling Wu; Ling Lei; Hongxiang Zhao; Qiyu Zhang; Yuanxia Wang; Yao Chen; Chencong Nie; Jiquan Zhang (PLoS ONE, 2025)
Objective To understand the current status of dignity impairment in elderly patients with incontinence-associated dermatitis and to systematically analyze the factors influencing it. Methods This study employed a cross-sectional survey design. From July 15th to 31st, 2024, a convenience sampling method was used to select elderly patients with incontinence-associated dermatitis (IAD) from 42 tertiary comprehensive medical institutions across 11 provinces and autonomous regions, including Sichuan, Zhejiang, and Guangdong. A general information questionnaire and a dignity assessment scale were used to gather data on participants’ demographic characteristics, clinical conditions, and dignity impairment symptoms. Results A total of 372 patients were effectively surveyed, of whom 131 exhibited symptoms of dignity impairment, resulting in an incidence rate of 35%. Multifactorial analysis revealed that Employment Status [OR = 4.183, 95% CI (2.233-7.837)], Primary Caregiver [OR = 1.451, 95% CI (1.005-2.095)], Respiratory System Disease [OR = 5.053, 95% CI (2.079-12.279)], and Nervous System Disease [OR = 2.452, 95% CI (1.206-4.985)] were risk factors for dignity impairment symptoms in elderly patients with incontinence-associated dermatitis. Conversely, Gender [OR = 0.488, 95% CI (0.295-0.807)] and Self-Reported Family Harmony [OR = 0.703, 95% CI (0.550-0.898)] were identified as protective factors against dignity impairment symptoms in this patient population. Conclusion Although the incidence of dignity impairment symptoms in elderly patients with incontinence-associated dermatitis is relatively low, the psychological trauma it causes cannot be overlooked. Healthcare professionals must actively establish and enhance prevention and management systems for this condition.